Case Series: Managing Severe Mental Illness in Disaster Situation: the Croatian Experience After 2020 Earthquake - Medved, Sara; Imširagić, Azijada Srkalović; Salopek, Igor; Puljić, Dragan; Handl, Hrvoje; Kovač, Marina; Peleš, Alma Mihaljević; Štimac Grbic, Danijela; Romančuk, Luka; MuŽić, Roberto; Zeeman, Laura Shields; Kuzman, Martina Rojnić (Frontiers in Psychiatry, 2022)
On the 29th of December 2020, amidst the COVID-19 pandemic, Petrinja in the Croatian Sisak-Moslavina County experienced a strong earthquake, resulting in a severe disruption in mental health service delivery. Specialized care community mental health teams were introduced days within the event with the aim to bridge the gap in psychiatric care that was severely disturbed in the region affected by the earthquake. Through a case series of patients with SMI, we describe how care was quickly deployed and delivered after a natural disaster and during a pandemic resulting in their functional recovery. Community mental health teams have the potential to provide feasible, comprehensive, and accessible mental health services and their continued implementation in the post-disaster period in Croatia could be beneficial for care management of people with severe mental illness.